Urban wetlands and their impact on city sustainability (Journal of Planner and Development, 2020)
Urban wetlands are one of the complex systems that provide many economic, social and environmental services to the city. In this research, the most important services provided by urban wetlands from the point of view of the urban planner were reviewed, and the types of these lands and their divisions according to the type of services provided by each type were presented. Environmental is represented in its ability to reduce the dangers of floods, mitigate the climate and reduce its negative impacts, purify water and deplete a lot of suspended impurities and pollutants, and social services such as recreational areas and beautiful landscapes that inspire joy and reassurance in the soul, as well as cultural areas and sports activities for many sports Games, fishing fun, and economic services are home to many types of plants and animals, as well as the economic values ​​of the services they provide as an infrastructure for many cities and provide a source of water sources for communities and sedimentation basins for sewage and sewage in addition to the economic values ​​of tourism and recreational activities for those lands, as well as identifying needs For each type and the appropriate spatial distribution for each type according to the Special standards and the use of GIS technologies to be included in the master plan for cities in order to achieve the goals of sustainable development for these cities.